Herencia de la resistencia al nematodo formador de nudos radiculares (Meloidogyne incognita Chitwood) en el cultivar de tomate Licato. (1989)
In order to do genetic characterization of the root-knot nematode Meloidogyne incognita resistance, exhibited by the tomato cultivar 'Licato', and using as resistance indexes the variables knot number and egg-masses number by plant, an inheritance study was carried out by using 'Licato' as resistant parent, 'Rutgers' as susceptible parent and the generations Fl and F2, as well as, backrosses from the Fl to both parents, employing in all the generations, 'Licato' as female. Besides the above an study of reciprocal effects was done with the direct and reciprocal hybrids between 'Licato' and 'Tropic' (susceptible parent). The studies were carried out under plastic root at ICA'S "La Selva" Experiment Station located at Rionegro (Antioquia, Colombia) at 2.100 meters above sea level. The obtained results, for the inheritance study, indicated that the resistance, measured for the two variables, is conditioned at least by two pair of genes with non-allelic interaction, being possible that the two evaluated variables are controlled by a group of genes with pleiotropic effects. The data for the several generations fitted a four parameteres model including m (mean population), d (additive effect), h (dominance effect) and j (additive x dominance interaction). Besides the above, reciprocal effects for both variables were found, which indicates also the existance oi cytoplasmic factors conditioning the resistance observed in this study.